Preceramic riverside hunter-gatherers and the arrival of Neolithic farmers in northern Luzon. (August 2022) - Hung, Hsiao-chun; Tsang, Cheng-hwa; Deng, Zhenhua; Bolunia, Mary Jane Louise A.; Santiago, Rey A.; Carson, Mike T.; Bellwood, Peter
Abstract: Abstract : The most westerly Pacific island chain, running from Taiwan southwards through the Philippines, has long been central in debates about the origins and early migrations of Austronesian-speaking peoples from the Asian mainland into the islands of Southeast Asia and Oceania. Focusing on the Cagayan Valley of northern Luzon in the Philippines, the authors combine new and published radiocarbon dates to underpin a revised culture-historical synthesis. The results speak to the initial contacts and long-term relationships between Indigenous hunter-gatherers and immigrant Neolithic farmers, and the question of how the early speakers of Malayo-Polynesian languages spread into and through the Philippines.